Progress in Mimetic Studies of Cell Adhesion and the Mechanosensing - Smith, Ana-Suncana; Sackmann, Erich (ChemPhysChem, 2009)
Vesicle-substrate adhesion has been studied for over two decades with the motivation to understand and mimic cell adhesion. In recent years, with progress in theoretical modelling, the development of experimental techniques, and improved data-analysis procedures, considerable advances hove been made in the understanding of the adhesion process. It is this progress which constitutes the focus of this review.
Keywords: adhesion; cells; mechanosensing; specific binding; vesicles